Avaliação do cumprimento das regras da autorregulamentação publicitária propagandas de bebidas alcoólicas veiculadas na televisão brasileira - Vendrame, Alan [UNIFESP] (2010)
Introduction: the relationship of alcoholic beverages advertisements and alcohol consumption by children and adolescents as well as the control system of this type of advertising are covered in this study. Objectives: to investigate the relationship of alcohol advertisements broadcast on Brazilian television with the consumption of alcohol by adolescents. Evaluate compliance with the rules of the marketing self-regulated code in the top 5 most popular beer advertisements among adolescents and to develop methodology for independent monitoring of these advertisements. Perform a systematic review of international literature on self-regulation and alcohol advertisements. Method: the methodology was divided in three parts. At first, 133 adolescents aged 14 to 17 years saw 32 advertisements for beer and ice and recorded for each one, how much they liked (scores of zero to ten) and how many times it had seen before (attractiveness and exposure, respectively); also recorded demographic data and alcohol consumption. In the second part, 232 adolescents in the same age group watched the first five most popular commercial displayed (previous step) and responded questions designed to assess the rules of the Brazilian self-regulated code. In the last part, were performed a literature review of published articles on the self-regulation for alcohol advertisements, between the years 1999 and 2010 in Medline, SciELO, Camy and Google Scholar. Results: the five most popular advertisements had already been assisted previously, which did not occur with the least popular, besides, among the five most popular grades were assigned significantly higher for adolescents who consumed beer in the last month. The study also showed that the five most popular advertisements by adolescents significantly violated the rules of the Brazilian self-regulated code: 16 rules evaluated, 11 were violated. Similarly, the works gathered in a systematic review of international literature showed that self-regulation is failure. Conclusions: the study presented groundbreaking data on the relationship between alcohol advertising in Brazil and alcohol consumption by adolescents and developed a method that may allow independent monitoring of compliance of self-regulation on alcohol advertisements, for low cost and by untrained people. These data provide important scientific evidence, supporting the implementation of public policies to prevent alcohol use by children and adolescents as well as to control the advertising of alcoholic beverages in Brazil.